Forecasting intensifying disturbance effects on coral reefs. (25th March 2020) - Vercelloni, Julie; Liquet, Benoit; Kennedy, Emma V.; González‐Rivero, Manuel; Caley, M. Julian; Peterson, Erin E.; Puotinen, Marji; Hoegh‐Guldberg, Ove; Mengersen, Kerrie
Abstract: Anticipating future changes of an ecosystem's dynamics requires knowledge of how its key communities respond to current environmental regimes. The Great Barrier Reef (GBR) is under threat, with rapid changes of its reef‐building hard coral (HC) community structure already evident across broad spatial scales. While several underlying relationships between HC and multiple disturbances have been documented, responses of other benthic communities to disturbances are not well understood. Here we used statistical modelling to explore the effects of broad‐scale climate‐related disturbances on benthic communities to predict their structure under scenarios of increasing disturbance frequency. We parameterized a multivariate model using the composition of benthic communities estimated by 145, 000 observations from the northern GBR between 2012 and 2017. During this time, surveyed reefs were variously impacted by two tropical cyclones and two heat stress events that resulted in extensive HC mortality. This unprecedented sequence of disturbances was used to estimate the effects of discrete versus interacting disturbances on the compositional structure of HC, soft corals (SC) and algae. Discrete disturbances increased the prevalence of algae relative to HC while the interaction between cyclones and heat stress was the main driver of the increase in SC relative to algae and HC. Predictions from disturbance scenarios included relative increases in algae versus SC that varied by the frequency and types of disturbance interactions. However, high uncertainty of compositional changes in the presence of several disturbances shows that responses of algae and SC to the decline in HC needs further research. Better understanding of the effects of multiple disturbances on benthic communities as a whole is essential for predicting the future status of coral reefs and managing them in the light of new environmental regimes. The approach we develop here opens new opportunities for reaching this goal. Abstract : We present a novel approach to estimate the effects of disturbances on benthic communities and predict their structure under scenarios of increasing disturbance frequency. The model was parameterized using 145, 000 observations of benthic communities from the Great Barrier Reef. During 2012–2017, surveyed coral reefs were variously impacted by two tropical cyclones and two heat stress allowing us to estimate changes in reef composition when there is not enough time for hard corals to recover. Better understanding of the effects of multiple disturbances on benthic communities as a whole is essential for predicting the future status of coral reefs.